ANALISIS KESULITAN BELAJAR MATEMATIKA PADA KURIKULUM MERDEKA BELAJAR DIKELAS IV SD KARANG MULYA 2 - Setianingsih, Eka; Fitri, Ayu; Prihamdani, Depi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the factors of difficulty learning mathematics in the 2013 curriculum for class IV of SD Negeri Karang Mulya 2, Karawang Regency. This research is qualitative field research with descriptive analysis techniques. The subjects of this research were class IV students, class IV homeroom teachers, and the school principal. The object of this research is to analyze the factors of students' mathematics learning difficulties in the 2013 Curriculum and the efforts that teachers must make to overcome students' learning difficulties. Data collection using observation methods, interview methods and documentation methods. Meanwhile, data analysis uses Miles and Hubermen's descriptive analysis which consists of: data collection, data reduction, data presentation and conclusion/verification. The findings of this research prove that 1) There are factors of difficulty learning mathematics in the 2013 Curriculum for class IV SD Negeri Karang Mulya 2 Karawang Regency, which consist of internal and external factors for students. 2) Knowing the efforts made to overcome mathematics learning difficulties in the 2013 Curriculum for class IV of Karang Mulya State Elementary School 2. From this research, findings emerged that (1) There are factors of mathematics learning difficulties in the 2013 Curriculum experienced by students of class IV of Karang State Elementary School Mulya 2, (2) Various efforts must be made by teachers to overcome difficulties in learning mathematics in the 2013 Curriculum in class IV of SD Negeri Karang Mulya 2.